Plan de negocio para la creación de una empresa de asesorías en auditoria y revisoría fiscal en la ciudad de Santa Marta (2022)
Starting from the Statutory Auditor as an institution and not only as a body or a simple control activity, those practices are identified that, based on the audit control, must be carried out to add value in companies and maintain the defense of assets and corporate interests. The exercise of the Statutory Auditor in Magdalena has been widely questioned due to doubts about its effectiveness in controlling business or organizational activities. Currently there are various negative interpretations of the Statutory Auditor in the department of Magdalena, the most outstanding tend to assimilate it as an external audit, recognized as a control entity or institution in crisis due to its lack of credibility caused by a questionable performance of companies facing bankruptcy proceedings; especially in the financial sector, where it has been more acute.